Analisis Preferensi Konsumen Industri terhadap Selada Hidroponik Produksi Kebun Bertani Agro Farm Kota Semarang - Amanda, Putri Rizkia; Mukson, Mukson; Setiadi, Agus (Universitas Galuh, 2025)
The purpose of this study was to analyze the preferences of industrial consumers and to analyze the effect of price, quality, availability, type of processed product, sales turnover, and taste on consumer preferences of the hydroponic lettuce industry produced by Kebun Bertani Agro Farm, Semarang City. The research method used was a survey. The study was conducted in October - November 2024 in Mijen District, Semarang City. The determination of the research location was carried out purposively. The data collection method was carried out by interview using a closed questionnaire on a Likert scale. The sampling method used a census sampling technique, namely industrial consumers who had become regular customers of Bertani Agro Farm. The number of respondents used was 43 industrial consumers consisting of 18 kebab MSMEs, 5 food stalls, 5 catering, and 15 restaurants. The types of data used were primary and secondary. Data analysis used data tabulation calculations and analyzed using the SPSS program. The data analysis methods used were conjoint analysis and multiple linear regression. The test analysis used was the classical assumption (Shapiro-Wilk normality, linearity, multicollinearity, and heteroscedasticity) and hypothesis testing. Based on the research results, it was found that the most important attributes in order were price, availability, and quality, with a combination of product attributes that industrial consumers consider most for hydroponic lettuce is that it has a price of IDR 25,000, lettuce quality with green leaves, no holes and has a shelf life of ≤ 3 days, and availability that exceeds demand. Having a significance value of the t-test and F-test of less than 0.05, indicating that both partially and simultaneously all X variables have a significant effect on industrial consumer preferences. The adjusted R square value is 0.976, which means that 97.6% of the variation or change in consumer preferences is explained by the variables and the rest is not analyzed in the model.